Fabrication And Characterization Of Poly(3-Hydroxybutyrate-Co-4- Hydroxybutyrate/Collagen) Blended Microspheres For Tissue Engineering Application - Omar, Noor Aidda (2023)
The scaffold is one of the main components in tissue engineering that provides structural support for cell attachment and tissue development. However, due to poor transportation of nutrients and waste products in the scaffold, cell necrosis often occurs in the center of large sized scaffolds. Additionally, transplanting scaffolds usually involves invasive surgery which can incur a prolonged healing period and is inconvenient to the patient. Hence, by using small injectable scaffold which can provide the space for movement of oxygen and waste product such as microspheres can reduce the cell necrosis. Furthermore, the injectablity scaffold also can facilitate the surgical procedure thus speed up the time recovery and convenient to the patient.